Investigation the maximum load capacity of the tail-shaft on the apron feeder using Solidwork simulations - Hidayat, Nailul; Primawati; Myint, Phyo Wai (Journal of Engineering Researcher and Lecturer, 2023)
The tail-shaft is one of the components of the apron feeder on the conveyor. Its role is quite significant, as it includes a take-up system to adjust the tension and slackness of the chain on the sprocket against the Lamella. Based on observations in a mining industry, it was found that tail-shaft damage frequently occurs, likely due to the excess load carried by the conveyor. Therefore, researchers were interested in investigating the maximum capacity of the tail-shaft. The research was conducted using the Finite Element Analysis method with Solidworks Research License. The material used for the tail-shaft is DIN 1.0038. Torque variations tested on the tail-shaft were from 42,000 N.m to 58,000 N.m. Based on the simulation results, the maximum torque that the tail-shaft can withstand is 54,000 N.m with a safety factor value greater than 1, whereas when given a torque of 58,000 N.m, the safety factor value is less than 1. The tail-shaft experiences a maximum stress that exceeds the yield strength of DIN 1.0038 material, which can cause damage to the material. The initial damage appears at the end of the shaft due to the use of chamfer. This is known based on the results of simulations that have been conducted.